Implementasi Algoritma Data Encryption Standart (DES) Dalam Pengamanan Data Karyawan Ramayana Department Store - Alan Boy Sandy Damanik; Indra Gunawan; Bahrudi Efendi Damanik; Sumarno Sumarno; Dedy Hartama (Journal of Computer System and Informatics (JoSYC), 2020)
Employee data is information that is very confidential because it contains important information about employees and their institutions. Computers are currently the main component in the company that is able to store data, speed up work, improve the quality and quantity of services, simplify the transaction process, and others. But in terms of computer security still has several loopholes that allow a person or group to easily retrieve data or information on the computer. To avoid data theft and manipulation, a security system must be implemented. Cryptography is a study of how to change information from normal conditions / forms (can be understood) into a form that cannot be understood. One method that can be used to secure messages / information is the DataEncryption Standard (DES). The application of the DES cryptography algorithm in securing Civil Servants data shows that this algorithm can generate encryption that cannot be understood by humans and produces the exact decryption of the initial plaintext input